Chemical Literacy Skill of High School Students on the Solution Chemistry - Senna Prasemmi; Sri Rahayu; Fauziatul Fajaroh; Saeed Almuntasheri (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
This research aimed to develop a multiple-choice chemical literacy test on solution chemistry as an instrument that specifically focuses on learners' knowledge and competency aspects; applying the test instrument by surveying 12th-grade high school students. The development of the test instrument adapted the R&D model by Borg and Gall. The Cronbach's Alpha reliability of the test was obtained after small-scale and wide-scale trials are 0.793 and 0.833, respectively, with 35 valid items. Data were collected using random cluster sampling with a total of 463 respondents. The result shows that the mean score of chemical literacy for the students in this study is 46.27. This indicated that the students' level of chemical literacy is low, and further improvement is required.